American Protestants and TV in the 1950s - Rosenthal, M. author. aut Link
XII, 179 p.
Keywords: Americans in the 1950s faced the challenge of negotiating the new medium's place in the home and in American culture in general. Using the American Protestant experience of the introduction of television, Rosenthal illustrates the importance of the interplay between a new medium and its users.